Analisis Pengaruh Bantuan Progam Sembako Terhadap Prevalensi Stunting di Indonesia - Novalianita, Putri; Handayani, Dwini (Jurnal Manajemen Bisnis dan Keuangan, 2023)
Program Sembako is one of the food assistance instruments to reduce the burden on household expenses in accessing food as well as to meet adequate nutritional needs as an effort to prevent stunting. This study aims to analyze the effect of the basic food program on the stunting prevalence rate in Indonesia. The method used is Two-Stage Least Squares using STATA 16 in processing to test the significance of research. The results of the first stage IV2SLS show that there is a significant positive relationship between the Program Sembako and adequate nutritional intake, then the results of the second stage show that the higher the adequacy of household nutritious food intake, the lower the prevalence of stunting in Indonesia. In addition, there is a significant effect of the BCG vaccine and ownership of proper sanitation on the prevalence of stunting. Program Sembako will reduce the expenditure burden of poor families in terms of food, so that some of the basic needs of the poor can be met. On the other hand, developing the types of foodstuffs obtained from this program will be able to improve community nutrition, especially for children from an early age so that it will have an effect on reducing stunting.